How Safe Are Principles and Good Corporate Governance Applied in an Indonesian Zakat Institution? - Rahman, Adi; Deden Dinar Iskandar; Budi Santosa, Purbayu (Universitas Muhammadiyah Yogyakarta, 2025)
This study examines the application of the 3 Aman Principles, namely Aman Syar’i (compliance with Islamic law), Aman Regulation (compliance with legal standards), and Aman NKRI (commitment to the integrity of the Unitary State of the Republic of Indonesia), together with Good Corporate Governance (GCG) principles at one of the National Zakat Boards (BAZNAS) in Indonesia. A descriptive qualitative method with a case study approach was employed, involving separate interviews with five BAZNAS officials, direct observation, document analysis, and open-ended questionnaires to zakat payers (muzakki). Data validity was ensured through source and technique triangulation. The novelty of this research lies in integrating the 3 Aman Principles, which reflect Indonesia’s distinctive approach to zakat governance, with GCG principles commonly used in corporate governance and recognized internationally. This integration offers a perspective rarely discussed in prior studies. The findings show that compliance and accountability have been effectively implemented, although improvements are needed in financial reporting transparency and strategies to engage potential zakat payers. Theoretically, this study contributes to the literature by demonstrating the synergy of national and international governance principles in enhancing institutional trust. Practically, the results guide zakat institutions in developing governance strategies that strengthen public trust.